Maternal alcohol consumption and offspring DNA methylation: findings from six general population-based birth cohorts. (January 2018) - Sharp, Gemma C; Arathimos, Ryan; Reese, Sarah E; Page, Christian M; Felix, Janine; Küpers, Leanne K; Rifas-Shiman, Sheryl L; Liu, Chunyu; ,; Burrows, Kimberley; Zhao, Shanshan; Magnus, Maria C; et al.
Aim: Alcohol consumption during pregnancy is sometimes associated with adverse outcomes in offspring, potentially mediated by epigenetic modifications. We aimed to investigate genome-wide DNA methylation in cord blood of newborns exposed to alcohol in utero .Materials & methods: We meta-analyzed information from six population-based birth cohorts within the Pregnancy and Childhood Epigenetics consortium.Results: We found no strong evidence of association at either individual CpGs or across larger regions of the genome.Conclusion: Our findings suggest no association between maternal alcohol consumption and offspring cord blood DNA methylation. This is in stark contrast to the multiple strong associations previous studies have found for maternal smoking, which is similarly socially patterned. However, it is possible that a combination of a larger sample size, higher doses, different timings of exposure, exploration of a different tissue and a more global assessment of genomic DNA methylation might show evidence of association.